2014
DOI: 10.35536/lje.2014.v19.i1.a2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exchange Rate Volatility on Trade: A Panel Study on Pakistan’s Trading Partners

Abstract: This study investigates the impact of domestic and foreign currency-valued exchange rate volatility on the export and import demand functions with reference to Pakistan’s trading partners. We use GARCH-based exchange rate volatilities and the least-squares dummy variable technique with fixed-effects estimation to measure the volatility impact on both demand functions. The study evaluates a series of exchange rates from 1970:01 to 2009:12 to compare the long-run impact of volatility with that of the short run. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
(45 reference statements)
3
15
0
Order By: Relevance
“…In this regard, we utilise GARCH models for observing the news elements in the sample time series data. The GARCH models also understand the different types of dynamic behaviours of stock markets due to the good or bad news (Khan et al, 2014).…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…In this regard, we utilise GARCH models for observing the news elements in the sample time series data. The GARCH models also understand the different types of dynamic behaviours of stock markets due to the good or bad news (Khan et al, 2014).…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…2 Since Pakistan was one of the 12 countries included among Asian LDCs (Less Developed Countries), one comes to a conclusion that Pakistan's exports are not affected by exchange rate uncertainty. Khan et al (2014) is another panel study that assesses the impact of domestic and foreign-currency valued exchange rate volatility on Pakistan's exports to and imports from 29 partners (see their table CI) to concluded that When the US dollar was used as a vehicle currency, trade flows were adversely affected by volatility. However, when other currencies were considered, trade flows were not affected.…”
Section: The Literaturementioning
confidence: 99%
“…The local and foreign Exchange rates directly affect the real prices of production and goods traded among the nations in the world, as it shows the price paid when every transaction is performed. Similarly, domestic inflation has a vital part in setting the changing prices patterns of tradable goods (Jalil Khan, Parvez, and Shabib, 2014). For the developing nations, the issues concerning trade increase when the external factors appear in the form of "News" or "Shocks" and break the general flow of the international costs paid for the stocks or commodities.…”
Section: Impacts Of Foreign Exchange Rate Volatility On Car Exportmentioning
confidence: 99%